center is located at (-2,5) is:(x+2)^2 / 36 + (y-5)^2 / 64 = 1
The dimensions of the given ellipse are major axis 12 units long and parallel to the y-axis, minor axis 8 units long, and the center is located at (-2,5).Let us find the standard form equation of the ellipse. The standard form equation of an ellipse is given by:(x-h)^2 / a^2 + (y-k)^2 / b^2 = 1Where (h, k) is the center of the ellipse, a is the distance from the center to either the x-axis or the y-axis, and b is the distance from the center to the other axis. Therefore, for the given ellipse, the equation of the ellipse in standard form is:(x+2)^2 / 36 + (y-5)^2 / 64 = 1Thus, the standard form equation of the ellipse whose major axis is 12 units long and parallel to the y-axis, minor axis 8 units long, and center is located at (-2,5) is:(x+2)^2 / 36 + (y-5)^2 / 64 = 1.
Learn more about ellipse
#SPJ4
The elimination method is ideal for solving this system of equations. By which number must you multiply the second equation to eliminate the
yavariable, and what is the solution for this system?
x + 3y - 42
2x-y-14
OA. Multiply the second equation by-3. The solution is x = 12. y - 9.
ов.
Multiply the second equation by-2. The solution is x-12. y = 10.
OC.
Multiply the second equation by 2. The solution is x - 15, y = 9.
OD
Multiply the second equation by 3. The solution is x - 12. = 10.
Reset
Next
Answer:
D. Multiply the second equation by 3. The solution is x = 12, y = 10
Step-by-step explanation:
Given:
x + 3y = 42 (first equation)
2x - y = 14 (second equation)
To solve by elimination, starting with elimination of the y-variable, multiply the second equation by 3 to get a third equation.
2x - y = 14 (2nd eqn.) × 3
6x - 3y = 42 (3rd equation)
Add the 3rd equation and the 1st equation together.
x + 3y = 42 (first equation)
6x - 3y = 42 (3rd equation)
7x = 84
7x/7 = 84/7
x = 12
To find y, substitute x = 12 in the first equation
x + 3y = 42 (first equation)
12 + 3y = 42
12 + 3y - 12 = 42 - 12
3y = 30
3y/3 = 30/3
y = 10
Solution is x = 12, y = 10
Answer:
91 boys
Step-by-step explanation:
Given that the ratio of boys to girls = 7 : 2 = 7x : 2x ( x is a multiplier )
There are 65 more boys than girls , thus
7x = 2x + 65 ( subtract 2x from both sides )
5x = 65 ( divide both sides by 5 )
x = 13
There are 7 × 13 = 91 boys in the group
低于当地人民:或立场上有一些事情了!儿女情长的好了吗我想做出
B. y=-4
C. y=1
D. y=5